Kajian Filsafat Hukum Ketenagakerjaan: Rekonstruksi Nilai Keadilan dan Perlindungan Pekerja Dalam Sistem Hukum Indonesia - Suyanto Suyanto; Selamat Widodo; Agusta Awali Amruloh (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
This study analyzes the role of legal philosophy in shaping labor law and its implications for worker protection in Indonesia. Using a normative juridical method, the study finds that justice, legal certainty, and utility are not yet balanced. A progressive legal approach is required to ensure optimal worker protection.